Public health impact of the COVID-19 pandemic on the emergency healthcare system. (22nd June 2021) - Stirparo, G; Oradini-Alacreu, A; Migliori, M; Villa, G F; Botteri, M; Fagoni, N; Signorelli, C; Sechi, G M; Zoli, A
Abstract: Background: The Lombardy region has been the Italian region most affected by the coronavirus disease 2019 (COVID-19) pandemic in 2020. The emergency healthcare system was under deep stress throughout the past year due to the admission of COVID-19 patients to the emergency department (ED) and had to be thoroughly reorganized. Methods: We performed a retrospective descriptive analysis of patients admitted into the ED recorded in the Lombardy online regional portal called EUOL (Emergenza e Urgenza OnLine). We compared the data registered in the EUOL with the patients admitted to the EDs from 1 January 2019 to 31 December 2019 and from 1 January 2020 to 31 December 2020. Results: The number of admissions to the ED decreased by 32.5% in 2020 compared with 2019, reaching the lowest number in March and April. However, the percentage of patients hospitalized after ED significantly increased in 2020 compared with 2019 ( P  < 0.0001), reflecting the management of patients with a more severe clinical condition. More patients arrived at the ED by ambulance in 2020 (21.7% in 2020 versus 15.1% in 2019; P  < 0.0001), particularly during March and April. Conclusions: This analysis showed the importance of monitoring the pandemic's evolution in order to treat more critically ill patients, despite a lower number of patients.